Engineering graphics with AutoCAD 2013 - Bethune, James D.; Bethune, James D. (Boston, Massachusetts : Pearson, 2013)
This book teaches technical drawing and uses AutoCAD 2013 as its drawing instrument. Emphasis is on creating accurate, clear drawings.
Ch. 1. Getting Started -- Ch. 2. Fundamentals of 2D Construction -- Ch. 3. Advanced Commands -- Ch. 4. Sketching -- Ch. 5. Orthographic Views -- Ch. 6. Sectional Views -- Ch. 7. Auxiliary Views -- Ch. 8. Dimensioning -- Ch. 9. Tolerancing -- Ch. 10. Geometric Tolerances -- Ch. 11. Threads and Fasteners -- Ch. 12. Working Drawings -- Ch. 13. Gears, Bearings, and Cams -- Ch. 14. Fundamentals of 3D Drawing -- Ch. 15. Modeling -- Ch. 16. Projects.
Includes index.
Keywords: AUTOCAD